PEREMPUAN DALAM TIMBANGAN AL-QURAN DAN SUNNAH: WACANA PEREMPUAN DALAM PERSPEKTIF PENDIDIKAN ISLAM - Supriyadi, Tedi (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2018)
The androsentric cultural perspective seems to confirm that this world is a masculine world. From ancient times until now, the world as controlled by men. A man like a king and a slave woman. Ironically, the inauguration was done in the name of culture and even religion and moral. Indeed this is contrary to the spirit of Islam brought by the Prophet, one of which is lifting and glorifying women. On the basis of this idea this paper is intended to reconstruct the paradigm of women so that male hegemony over women can be eliminated and built egalitarian social and cultural constructions in the same position and role as the creature of God as the servant and caliph fil ardh. The realization of a new paradigm for women can be done by reinterpretation of sacred texts that have been interpreted in a culture of masculinity that is considered gender biased toward egalitarian interpretation. The strategy in the effort to build the paradigm can be pursued through the education path that education is always oriented to a change in both ways of thinking and behaving.